Right upper lobectomy in lung cancer with double aortic arch: A case report. Issue 8 (23rd June 2020) - Kawamoto, Nobutaka; Okita, Riki; Inokawa, Hidetoshi; Hayashi, Masataro; Furukawa, Masashi; Okada, Masanori; Okabe, Kazunori
Abstract: Double aortic arch (DAA) is a rare congenital anomaly of the heart and aorta in which a vascular ring that surrounds the trachea and esophagus is formed. In most patients, respiratory distress and dysphagia develop in childhood, and asymptomatic adult patients are rarely known. Herein, we describe a patient with lung cancer and DAA. A 66‐year‐old man who had DAA underwent video‐assisted thoracoscopic right upper lobectomy and mediastinal lymph node dissection for primary lung cancer. Lymph node dissection of the right upper mediastinum revealed that the right recurrent laryngeal nerve branched from the right vagus nerve just beneath the right aortic arch. Additionally, the right aortic arch narrowed the space surrounding the trachea, superior vena cava, and arch of the azygos vein, impeding the stapling of the truncus anterior artery and right upper lobe pulmonary vein with the video‐assisted thoracoscopic approach. Key points: Significant findings of the study: In double aortic arch, the recurrent laryngeal nerve branches from the vagus nerve just beneath the ipsilateral aortic arch. The right aortic arch narrows the space surrounding the trachea, superior vena cava, and arch of the azygos vein. What this study adds: The anatomy of a double aortic arch impedes mediastinal lymph node dissection on the ventral side of the trachea. Handling autosuture devices for stapling pulmonary arteries and veins is also difficult. Abstract : Double aortic arch (DAA) is a rare congenital anomaly of the heart and aorta in which a vascular ring that surrounds the trachea and esophagus is formed. A 66‐year‐old man who had DAA underwent video‐assisted thoracoscopic right upper lobectomy and mediastinal lymph node dissection for primary lung cancer. Lymph node dissection of the right upper mediastinum revealed that the right recurrent laryngeal nerve branched from the right vagus nerve just beneath the right aortic arch.